Transformasi Pendidikan Multikultural dalam Membangun Kesadaran Inklusif di Era Digital: Perspektif Sosiologi Pendidikan - Ahmad Salim Ulul Albab; Asnawan Asnawan; Syaiful Anwar; Futuh Muafi (Educational Journal, 2026)
Indonesia's multicultural society is confronted with increasingly complex challenges driven by the rapid advancement of the digital era, including the rise of intolerance, social polarization, identity politics, and the widespread dissemination of hate speech through digital media. These challenges indicate that the current education system has not yet effectively fostered the inclusive awareness required to manage diversity constructively. This study aims to analyze the transformation of multicultural education in fostering inclusive awareness in the digital era from the perspective of the sociology of education. The study employed a qualitative approach using a library research method. Data were collected from a wide range of scholarly sources, including books, national and international journal articles, and other relevant academic publications, and were analyzed through content analysis. The findings reveal that multicultural education should not be limited to the normative transmission of tolerance values but should be reoriented toward pedagogical transformation that promotes critical consciousness, social empathy, and students' dialogical competencies. A synthesis of the educational perspectives of Pierre Bourdieu, Paulo Freire, and Émile Durkheim demonstrates that education should be reconstructed through an inclusive curriculum, dialogical learning, the enhancement of critical digital literacy, and the transformation of teachers' roles as social mediators. This study proposes a conceptual model of multicultural education transformation that integrates these three theoretical perspectives as a strategic framework for strengthening students' inclusive awareness in responding to the challenges of an increasingly diverse digital society. The proposed model is expected to serve as a conceptual reference for developing educational policies and practices that are more democratic, humanistic, and socially just.